Implementing Information Technology, Information System And Its Application In Making The Blue Print for The One Stop Permission Services - Sri Agustina Rumapea; Humuntal Rumapea (Bandar Lampung University (UBL), 2012)
A complexity growing enterprise make the management in a bigger demanding to the IS function. They need access to the data anytime and anywhere easily, accurately and consistently in all departments. IS is encouraged to get the changes of business condition faster, and can act the data sharing within every department.The problem in using the support from IT, the investment for the IT and Information System (IS) are often in a wrong direction and decreasing of the strategy in IT and IS are often different from the enterprise business strategy. It is happened because the development of the IS, done without making the enterprise blue print first as the foundation for the development of the IS. So with the complexity of the enterprise development forces the enterprise to make continue customization to the building IS which of course need much financial support. IS duplication, no IS integration among them, and the difference platform among every IS; also become the failure factor an enterprise to get the optimal benefit from the using of IT and IS. Because of that, a blue print from the enterprise becomes something very important to be built as a foundation of the using IT and IS. The development architecture can be done in the beginning enterprise was shaped or even in the time where the enterprise is being run. Enterprise Architecture Planning (EAP) is a modern approach to do the planning for the data quality to achieve the IS mission. EAP is also a process of definition of some architecture such as data architecture, application architecture in using the information to support the business. The blue print, resulted together with EAP then can be used as the foundation in the IS development, by this we hope the IS which has been build can be adjusted with business strategy from the office of PPTSP so that the mission can be achieved from this publik services.